Kolorektalni rak - Dobnik, Gašper (Placebo, 2023)
Colorectal cancer (CRC) is one of the most widespread cancers in the world, and according to the International Organization for Cancer Research, GLOBOCAN, it ranks as the third most common and second deadliest cancer. The main reason for new cases is mainly attributed to the spread of the »Western« lifestyle. The incidence is falling in the elderly, but there is a noticeable increase in cases in the population under 50, so experts recommend lowering the starting age for testing from 50 to 45 years. Obesity, a sedentary lifestyle, a diet with a high content of red meat and saturated fat, alcohol and tobacco are important factors in the formation and development of CRC, but they can be limited and changed quite easily. Despite the large number of patients with this type of cancer, mortality has been declining in recent years, which is mainly due to the new methods of early cancer detection and treatment methods, among which surgical interventions are still the primary treatment.
Keywords: dejavniki tveganja; Epidemiologija; kolorektalni rak; Rak debelega črevesa in danke; Zdravljenje